Analisis Efektivitas Pengendalian Biaya, Perputaran Modal Kerja, dan Rentabilitas Ekonomi Menggunakan Regresi Data Panel - Rizka Hadya; Nova Begawati; Irdha Yusra (JURNAL PUNDI, 2017)
Economic Rentability depend on the factor of the efficiency of cost control and working capital turnover (Khoyri, 2014; Vidiyastutik, 2013). This paper investigatesthe impact of cost control effectiveness and working capital turnover on Economic Rentability. The type of data used was quantitative data taken from the company's annual financial statements. Using panel data for 14companiesthat is all manufacturing companies of metal sub sector and the like that listed on Indonesia Stock Exchange and the observation period from 2012to 2016, we tested the relationships between the efficiency of cost control and working capital turnover by building panel model. The sampling technique used is purposive sampling. Meanwhile, the statistical method used is multiple linear regression analysis. Our findings showed that the efficiency of cost control does not have a significant effect on Economic Rentability. The results of this paperis indicated by the significance value of the efficiency of cost control greater than alpha (0.869> 0.05). This study also reveals that Working Capital Turnover has a significant effect on Economic Profitability. The statistical test shows that the significance value of Working Capital Turnover is smaller than alpha (0.000 <0.05).